Question
7) \( (-q)^{3}=-\left(q^{3}\right)= \) 8) \( (-q)^{2}=q^{2}= \)
Ask by Dawson Williams. in Colombia
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
7) \( (-q)^{3} = -q^{3} \)
8) \( (-q)^{2} = q^{2} \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Bonus Knowledge
When you raise a negative number to an odd power, the result is negative. So, \( (-q)^{3} \) simplifies to \( -q^{3} \), showcasing the quirky behavior of odd exponents and how they keep the negativity intact! On the other hand, raising a negative number to an even power yields a positive result. This means \( (-q)^{2} \) simplifies to \( q^{2} \), perfectly demonstrating how even exponents cheerfully erase any sign at the entrance!